A prospective study to assess the value of liquid chromatography-tandem mass spectrometry in the management of paediatric poisoning at Red Cross War Memorial Children's Hospital, Cape Town, South Africa - Washaya, Norbertta Nzwisisayi (Department of Paediatrics and Child Health, 2021)
Background: Paediatric poisoning is a common presentation to emergency departments worldwide. There is a paucity of data on the role of liquid chromatography-tandem mass spectrometry (LC-MS/MS), in the management of paediatric poisoning in low-and middle-income countries (LMICs). In high-income countries, most studies are retrospective, and few include children. Objective: The study describes the prevalence of liquid chromatography-tandem mass spectrometry confirmed paediatric poisoning at Red Cross War Memorial Children's Hospital, Cape Town, South Africa. Methods Children admitted with suspected poisoning between 1 January 2017 and 31 December 2017, were recruited. All patients had a urine and/or blood sample sent for LC-MS/MS toxicology. Data collected included demographic data, clinical features, investigations, management, outcome and social interventions. Results 152 children, with median age of 39 (IQR 25 -61) months were enrolled of which 128 (84%) were poisoning cases. Of the 128 poisoning cases, 88 (69%) presented with a history of ingesting a known substance, 16(12%) an unknown substance and 24(19%) were cases of occult poisoning. LC-MS/MS was able to identify a substance in 92% of the cases of occult poisoning. In those who had presented with a seemingly known substance, LC-MS/MS found a different substance in 15 cases. LC-MS/MS was also able to detect multiple drugs in 40 patients. Of the poisoning cases, six (5%) cases were attempted homicide cases and 5 (4%) cases were attempted suicide cases. No children died. Individualized social interventions were instituted in poisoning cases. Emergency placement safety reasons was required in 6 children. Conclusion: When the limitations are known, LC-MS/MS is useful in identifying cases of occult poisoning; identifying patients who have ingested multiple substances and/or an unknown substance and when targeted towards child protection. As LC-MS/MS is an expensive test, it should be used judiciously in LMICs.